HUBUNGAN KESIAPAN MENGAJAR MAHASISWA PPLK SENI RUPA DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SENI BUDAYA DI SMP NEGERI KOTA PADANG - FANI RAHMI DELVIRA, Drs. Wisdiarman, M.Pd., Dra. Ernis, M.Pd. (Serupa The Journal of Art Education, 2017)
This study aims to determine the relationship of preparedness to teach students PPLK Arts with student learning outcomes in Arts subjects in SMP Negeri Padang. This type of research is correlational, this study tries to lift and analyze the situation on the ground. Retrieving data using random sampling techniques. Data were collected by questionnaire and learning outcomes. The findings in this study show that: the readiness to teach students PPLK Arts has a high correlation value to student learning outcomes. That is relationship readiness to teach students PPLK Arts has a significant relationship with student learning outcomes in Arts subjects in SMP Negeri Padang. It can be concluded that the readiness to teach art students in performing PPLK very important role in improving student learning hasi.Keywords: Readiness PPLK student teaching and learning outcomes